Peningkatan Pemahaman Siswa SMK N 2 Semarang Sebagai Pemilih Pemula Menjadi Pemilih Yang Cerdas Pada Pilkada 2024 - Sukimin, Sukimin; Sihotang, Amri Panahatan; Mulyani, Tri (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2025)
The political participation of the younger generation, particularly first-time voters, plays a strategic role in shaping the direction of democracy in Indonesia. Through a community service program conducted at SMK N 2 Semarang, efforts were made to enhance students' understanding as first-time voters in preparation for the 2024 Regional Elections (Pilkada). This activity aimed to equip students with knowledge about the electoral process, the importance of their role as first-time voters, and how to become rational voters who are not easily influenced by short-term political interests. The implementation method consisted of three stages: pre-activity preparation, the main activity through lectures and discussions, and evaluation using pre-tests and post-tests to measure the level of students’ understanding. The results showed a significant improvement, with an average increase in understanding of 66.1% after the activity. These findings indicate that political literacy and outreach activities are effective in increasing awareness and readiness among students to exercise their voting rights wisely and responsibly. It is hoped that similar initiatives can be carried out sustainably to foster a generation of voters who are critical, rational, and uphold high integrity in the democratic process. Keywords: First-Time Voters; 2024 Regional Elections; Political Literacy.